Scroll back to the top

Virtual Math Learning Center Logo

Practice Problems for Module 12

Sections 11.10 and 11.11

Directions. The following are review problems. We recommend you work the problems yourself, and then click "Answer" to check your answer. If you do not understand a problem, you can click "Video" to learn how to solve it. You can also follow the link for the full video page to find related videos. 
  1. Find the Maclaurin series of \(f(x)=x^2\cos^2(3x)\).​

    \(\displaystyle f(x)=\frac{x^2}{2}+\sum_{n=0}^\infty \frac{(-1)^n6^{2n}}{2\cdot(2n)!} x^{2n+2}\)


    To see the full video page and find related videos, click the following link.
    WIR 20B M152 V79


  2. Express \(\displaystyle \int_0^{2/3} \! x^3\sin\left(x^2\right) \, dx\) as an infinite series.​

    \(\displaystyle \int_0^{2/3} \! x^3\sin\left(x^2\right) \, dx=\sum_{n=0}^\infty \frac{(-1)^n}{(4n+6)(2n+1)!} \left(\frac{2}{3}\right)^{4n+6}\)
    Video Errata: The upper limit of integration is \(2/3\), but the presenter writes \(3/2\) throughout the problem. The final answer is correct if you replace the \(3/2\) with \(2/3\).
     

    To see the full video page and find related videos, click the following link.
    WIR 20B M152 V80


  3. Find the Taylor series of \(\displaystyle f(x)=\frac{3}{(4x-5)^6}\) centered at \(x=2\).

    \(\displaystyle f(x)=\sum_{n=0}^\infty \frac{(-1)^n\cdot(n+1)(n+2)(n+3)(n+4)(n+5)\cdot4^n}{120\cdot3^{n+5}}(x-2)^n\)

    To see the full video page and find related videos, click the following link.
    WIR 20B M152 V81


  4. Find the Taylor series of \(\displaystyle f(x)=\left(x^2-x\right)e^x\) centered at \(x=1\).

    \(\displaystyle f(x)=\sum_{n=0}^\infty \frac{n^2e}{n!}(x-1)^n\)

    To see the full video page and find related videos, click the following link.
    WIR 20B M152 V82


  5. Find the \(4^{\textrm{th}}\) degree Taylor polynomial, \(T_4(x)\), for \(\displaystyle f(x)=e^{-3x}-2-3x\) centered at \(x=4\).

    \(\begin{align}\displaystyle T_4(x)=&\left(e^{-12}-14\right)-\left(3e^{-12}+3\right)(x-4)+\frac{9}{2}e^{-12}(x-4)^2\\&-\frac{9}{2}e^{-12}(x-4)^3+\frac{27}{8}e^{-12}(x-4)^4\end{align}\)

    To see the full video page and find related videos, click the following link.
    WIR 20B M152 V83